Positive electrode active material for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery
By incorporating metal elements with a specific ionic radius into lithium transition metal composite compounds, the battery's initial voltage is increased and voltage degradation during charge/discharge cycles is minimized, improving battery performance.
Patent Information
- Application Number
- JP2021566839
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-24
- Filing Date
- 2020-10-13
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2040-10-13
AI Technical Summary
Batteries using Li-excess positive electrode active materials face a decrease in battery voltage due to repeated charging and discharging, which affects their performance.
Incorporating metal elements with an ionic radius of 0.6 Å or more into lithium transition metal composite compounds stabilizes the structure, increasing the initial voltage while suppressing voltage drops during charge/discharge cycles.
The proposed positive electrode active material maintains higher initial voltage and reduces voltage degradation over cycles, enhancing battery performance.
Smart Images

Figure 0007617515000003 
Figure 0007617515000001 
Figure 0007617515000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a positive electrode active material for a non-aqueous electrolyte secondary battery, and a secondary battery using the positive electrode active material for a non-aqueous electrolyte secondary battery. [Background technology]
[0002] Conventionally, lithium transition metal complex compounds have been widely used as positive electrode active materials for secondary batteries such as lithium ion batteries, and Li-rich positive electrode active materials containing a large amount of Li have been attracting attention as high-output secondary batteries. However, batteries using Li-rich positive electrode active materials have a problem in that the battery voltage decreases due to repeated charging and discharging. Patent Document 1 discloses a technology for suppressing the decrease in battery voltage due to charge and discharge cycles by improving the composition of Li-rich positive electrode active materials. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 6342161 Summary of the Invention
[0004] The initial voltage of the battery using the Li-excess positive electrode active material disclosed in Patent Document 1 was low at about 3.58 V.
[0005] The positive electrode active material for a non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure includes a lithium transition metal composite compound. The lithium transition metal composite compound is represented by the general formula Li x Mn y Ni z Me α O a F b (wherein 1≦x≦1.2, 0.4≦y≦0.8, 0≦z≦0.4, x+y+z=2, 0<α≦0.05, 1.8≦a≦2, 1.8≦a+b≦2.2, and Me represents at least two elements selected from metal elements excluding Li, Mn, and Ni), and Me contains at least one element having an ionic radius of 0.6 Å or more.
[0006] A nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure includes a positive electrode containing the above-described positive electrode active material for nonaqueous electrolyte secondary batteries, a negative electrode, and a nonaqueous electrolyte.
[0007] According to the positive electrode active material for a nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure, it is possible to increase the initial voltage of the secondary battery while suppressing a decrease in the battery voltage due to charge / discharge cycles. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a longitudinal sectional view of a cylindrical secondary battery as one example of the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Li-excess positive electrode active materials, in which a part of the transition metal layer of a lithium transition metal composite compound having a layered rock salt structure is replaced with Li, have been attracting attention as materials for high-output secondary batteries. However, there is a problem that the output of the battery decreases when charging and discharging are repeated. As a result of intensive research into such problems, the present inventors have found that the structure of the lithium transition metal composite compound is stabilized by dissolving a metal element having an ionic radius of 0.6 Å or more in solid solution, and that the solid solution is stabilized by including two or more metal elements having an ionic radius of 0.6 Å or more. As a result, the inventors have come up with the following positive electrode active material for non-aqueous electrolyte secondary batteries, which can increase the initial voltage of the secondary battery while suppressing the decrease in battery voltage due to charge and discharge cycles.
[0010] The positive electrode active material for a non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure includes a lithium transition metal composite compound. The lithium transition metal composite compound is represented by the general formula Li x Mn y Ni z Me α O a F b(wherein 1≦x≦1.2, 0.4≦y≦0.8, 0≦z≦0.4, x+y+z=2, 0<α≦0.05, 1.8≦a≦2, 1.8≦a+b≦2.2, and Me represents at least two elements selected from metal elements excluding Li, Mn, and Ni), and Me contains at least one element having an ionic radius of 0.6 Å or more.
[0011] In the following, an example of an embodiment of a cylindrical secondary battery according to the present disclosure will be described in detail with reference to the drawings. In the following description, specific shapes, materials, values, directions, etc. are examples for facilitating understanding of the present disclosure, and can be appropriately changed according to the specifications of the cylindrical secondary battery. In addition, the exterior body is not limited to a cylindrical shape, and may be, for example, a rectangular shape. In addition, in the following description, when multiple embodiments and modified examples are included, it is assumed from the beginning that the characteristic parts of those embodiments and modified examples will be used in appropriate combination.
[0012] Fig. 1 is an axial cross-sectional view of a cylindrical secondary battery 10 as one example of an embodiment. In the secondary battery 10 shown in Fig. 1, an electrode body 14 and a non-aqueous electrolyte (not shown) are housed in an exterior body 15. The electrode body 14 has a wound structure in which a positive electrode 11 and a negative electrode 12 are wound with a separator 13 interposed therebetween. In the following description, for convenience of explanation, the sealing body 16 side will be referred to as the "upper" and the bottom side of the exterior body 15 as the "lower".
[0013] The opening end of the exterior body 15 is closed with the sealing body 16, so that the inside of the secondary battery 10 is sealed. Insulating plates 17 and 18 are provided above and below the electrode body 14, respectively. The positive electrode lead 19 extends upward through the through hole of the insulating plate 17 and is welded to the underside of the filter 22, which is the bottom plate of the sealing body 16. In the secondary battery 10, the cap 26, which is the top plate of the sealing body 16 electrically connected to the filter 22, serves as the positive electrode terminal. On the other hand, the negative electrode lead 20 extends through the through hole of the insulating plate 18 to the bottom side of the exterior body 15 and is welded to the inner bottom surface of the exterior body 15. In the secondary battery 10, the exterior body 15 serves as the negative electrode terminal. In addition, when the negative electrode lead 20 is installed at the terminal portion, the negative electrode lead 20 passes outside the insulating plate 18, extends to the bottom side of the exterior body 15, and is welded to the inner bottom surface of the exterior body 15.
[0014] The exterior body 15 is, for example, a cylindrical metal exterior can with a bottom. A gasket 27 is provided between the exterior body 15 and the sealing body 16 to ensure the sealing of the inside of the secondary battery 10. The exterior body 15 has a grooved portion 21 that supports the sealing body 16 and is formed, for example, by pressing a side portion from the outside. The grooved portion 21 is preferably formed in an annular shape along the circumferential direction of the exterior body 15, and supports the sealing body 16 on its upper surface via the gasket 27.
[0015] The sealing body 16 includes a filter 22, a lower valve body 23, an insulating member 24, an upper valve body 25, and a cap 26, which are stacked in this order from the electrode body 14 side. Each member constituting the sealing body 16 has, for example, a disk shape or a ring shape, and each member except the insulating member 24 is electrically connected to each other. The lower valve body 23 and the upper valve body 25 are connected to each other at their respective centers, and the insulating member 24 is interposed between their respective peripheral edges. When the internal pressure of the battery increases due to abnormal heat generation, for example, the lower valve body 23 breaks, and as a result, the upper valve body 25 swells toward the cap 26 and separates from the lower valve body 23, thereby cutting off the electrical connection between them. When the internal pressure further increases, the upper valve body 25 breaks, and gas is discharged from the opening 26a of the cap 26.
[0016] The positive electrode 11, negative electrode 12, separator 13, and non-aqueous electrolyte that constitute the secondary battery 10 will be described in detail below, in particular the positive electrode active material contained in the positive electrode mixture layer that constitutes the positive electrode 11.
[0017] [Positive electrode] The positive electrode 11 has a positive electrode core and a positive electrode composite layer provided on the surface of the positive electrode core. For the positive electrode core, a foil of a metal such as aluminum that is stable in the potential range of the positive electrode 11, a film with the metal disposed on the surface layer, or the like can be used. The positive electrode composite layer contains a positive electrode active material, a binder, and a conductive material, and is preferably provided on both sides of the positive electrode core except for the part where the positive electrode lead 19 is connected. The positive electrode 11 can be produced, for example, by applying a positive electrode composite slurry containing a positive electrode active material, a binder, a conductive material, and the like to the surface of the positive electrode core, drying the coating, and then compressing it to form a positive electrode composite layer on both sides of the positive electrode core.
[0018] Examples of the conductive material contained in the positive electrode mixture layer include carbon materials such as carbon black, acetylene black, ketjen black, and graphite. Examples of the binder contained in the positive electrode mixture layer include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide, acrylic resin, and polyolefin. These resins may be used in combination with cellulose derivatives such as carboxymethylcellulose (CMC) or its salt, and polyethylene oxide (PEO).
[0019] The positive electrode active material includes a lithium transition metal composite compound. The lithium transition metal composite compound preferably has a crystal structure of the O3 structure. For example, in terms of the stability of the crystal structure, the O3 structure is preferably 50% by volume or more of the crystal structure of the lithium transition metal composite compound, more preferably 90% by volume or more, even more preferably 98% by volume or more, and particularly preferably 100% by volume. Here, the O3 structure is a layered crystal structure in which lithium is present at the center of an oxygen octahedron, and there are three types of overlapping of oxygen and transition metal per unit cell, and it belongs to the space group R-3m or C2 / m.
[0020] Lithium transition metal complex compounds have the general formula Li x Mn y Ni z Me α O a F b(wherein 1≦x≦1.2, 0.4≦y≦0.8, 0≦z≦0.4, x+y+z=2, 0<α≦0.05, 1.8≦a≦2, 1.8≦a+b≦2.2, Me is at least two elements selected from metal elements other than Li, Mn, and Ni), and Me contains at least one element having an ionic radius of 0.6 Å or more. A secondary battery having a positive electrode containing such a positive electrode active material can suppress a decrease in battery voltage due to charge / discharge cycles while increasing the initial voltage of the secondary battery. The mole fraction of each element constituting the lithium transition metal complex compound can be measured, for example, by inductively coupled plasma (ICP) emission spectroscopy. The positive electrode active material may be composed of only the lithium transition metal complex compound, with the lithium transition metal complex compound being the main component. The positive electrode active material may contain a complex compound other than the lithium transition metal complex compound, as long as it does not impair the object of the present disclosure.
[0021] Me may contain at least one element selected from K, Sr, Ba, Bi, Ca, La, Pr, Y, Dy, Sn, and Zn. The ionic radius of these elements is 0.6 Å or more, as shown in Table 1. In addition, the ionic radius of Me is preferably 1.2 Å or less, from the viewpoint of easiness of solid-solubilization in the lithium transition metal composite compound.
[0022] [Table 1]
[0023] Me may contain at least one element selected from Sr, Ca, Y, and Sn, which can improve the initial voltage while suppressing the voltage drop due to charge-discharge cycles.
[0024] It is preferable that Me is substantially composed of at least three elements selected from Sr, Ca, Y, and Sn. This makes it possible to more reliably suppress the voltage drop due to charge / discharge cycles while improving the initial voltage. Here, "substantially composed of only A" means that A is the main component and may contain other elements than A within a range that does not impair the purpose of the present disclosure.
[0025] Me preferably contains at least an alkaline earth metal element. The alkaline earth metal elements are suitable because they are inexpensive and easily available. From the viewpoint of easiness of solid solution, Sr and Ca are more preferable.
[0026] It is preferable that the molar fraction α of Me satisfies 0.01≦α≦0.03. By making α≧0.01 or more, it is possible to more reliably suppress the voltage drop due to the charge / discharge cycle. In addition, by making α≦0.03, it is possible to increase the molar fractions of Mn and Ni, thereby making it possible to increase the capacity of the battery.
[0027] The lithium transition metal composite compound is produced by adding and mixing raw materials such as Li compounds, Mn compounds, Ni compounds, and Me compounds to a predetermined molar ratio, pulverizing and mixing the resulting mixture by mechanochemical treatment using a ball mill or the like, and firing the mixture after pulverization and mixing. The firing temperature of the mixture is preferably in the range of 700°C to 1000°C. The firing atmosphere is preferably an oxygen atmosphere or air. The lithium transition metal composite compound may be produced by firing the mixture to which the raw materials are added and mixed without carrying out mechanochemical treatment, but it is preferable to carry out mechanochemical treatment in terms of Me being easily dissolved in the mixture.
[0028] The Li compound is not particularly limited, but may be, for example, LiF, Li2CO3, LiOH, etc. The Mn compound is not particularly limited, but may be, for example, LiMnO2, Li2MnO 3、The Ni compound is not particularly limited, but may be, for example, LiNiO2, NiO, etc. The Me compound is not particularly limited, but may be, for example, an oxide of Me, specifically, MeO, Me2O3, MeO2, etc.
[0029] [Negative electrode] The negative electrode 12 has a negative electrode core and a negative electrode composite layer provided on the surface of the negative electrode core. For the negative electrode core, a foil of a metal such as copper that is stable in the potential range of the negative electrode, a film with the metal disposed on the surface layer, or the like can be used. The negative electrode composite layer contains a negative electrode active material and a binder, and is preferably provided on both sides of the negative electrode core except for the part to which the negative electrode lead 20 is connected. The negative electrode 12 can be produced, for example, by applying a negative electrode composite slurry containing a negative electrode active material and a binder to the surface of the negative electrode core, drying the coating, and then compressing it to form a negative electrode composite layer on both sides of the negative electrode core.
[0030] The negative electrode mixture layer contains, as the negative electrode active material, for example, a carbon-based active material that reversibly absorbs and releases lithium ions. Suitable carbon-based active materials are graphites such as natural graphite, such as flake graphite, lump graphite, and earthy graphite, and artificial graphite, such as lump artificial graphite (MAG) and graphitized mesophase carbon microbeads (MCMB). In addition, the negative electrode active material may be a Si-based active material composed of at least one of Si and a Si-containing compound, or a carbon-based active material and a Si-based active material may be used in combination.
[0031] The binder contained in the negative electrode mixture layer may be fluororesin, PAN, polyimide, acrylic resin, polyolefin, etc., as in the case of the positive electrode, but it is preferable to use styrene-butadiene rubber (SBR). In addition, it is preferable that the negative electrode mixture layer further contains CMC or a salt thereof, polyacrylic acid (PAA) or a salt thereof, polyvinyl alcohol (PVA), etc. Among them, it is preferable to use SBR in combination with CMC or a salt thereof, and PAA or a salt thereof.
[0032] [Separator] For example, a porous sheet having ion permeability and insulation is used for the separator 13. Specific examples of the porous sheet include a microporous thin film, a woven fabric, and a nonwoven fabric. The separator is preferably made of an olefin resin such as polyethylene or polypropylene, or cellulose. The separator 13 may be a laminate having a cellulose fiber layer and a thermoplastic resin fiber layer such as an olefin resin. The separator 13 may also be a multilayer separator including a polyethylene layer and a polypropylene layer, and may have a material such as an aramid resin or ceramic applied to the surface of the separator 13.
[0033] [Non-aqueous electrolyte] The non-aqueous electrolyte includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous electrolyte is not limited to a liquid electrolyte (electrolytic solution), and may be a solid electrolyte using a gel-like polymer or the like. The non-aqueous solvent may be, for example, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, or a mixed solvent of two or more of these. The non-aqueous solvent may contain a halogen-substituted product in which at least a part of the hydrogen of these solvents is substituted with a halogen atom such as fluorine.
[0034] Examples of the esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate; chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylates such as γ-butyrolactone and γ-valerolactone; and chain carboxylates such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), ethyl propionate, and γ-butyrolactone.
[0035] Examples of the above ethers include cyclic ethers such as 1,3 - dioxolane, 4 - methyl - 1,3 - dioxolane, tetrahydrofuran, 2 - methyltetrahydrofuran, propylene oxide, 1,2 - butylene oxide, 1,3 - dioxane, 1,4 - dioxane, 1,3,5 - trioxane, furan, 2 - methylfuran, 1,8 - cineole, crown ether, etc., and chain - like ethers such as 1,2 - dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o - dimethoxybenzene, 1,2 - diethoxyethane, 1,2 - dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1 - dimethoxymethane, 1,1 - diethoxyethane, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl, etc.
[0036] As the above - mentioned halogen - substituted compounds, it is preferable to use fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC), fluorinated chain - like carbonates, fluorinated chain - like carboxylic acid esters such as methyl fluoropropionate (FMP), etc.
[0037] The electrolyte salt is preferably a lithium salt. Examples of the lithium salt include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiCF3SO3, LiCF3CO2, Li(P(C2O4)F4), LiPF 6-x (C n F 2n+1 ) x (1 < x < 6, n is 1 or 2), LiB 10 Cl 10, LiCl, LiBr, LiI, lithium chloroborane, lower aliphatic lithium carboxylates, Li2B4O7, Li(B(C2O4)F2) and other borates, LiN(SO2CF3)2, LiN(C1F 2l+1 SO2)(C m F 2m+1 Examples of the lithium salt include imide salts such as LiPF6, LiPF2, and LiPF6 (where l and m are integers of 1 or more). The lithium salt may be used alone or in combination. Among these, LiPF6 is preferably used from the viewpoints of ion conductivity, electrochemical stability, and the like. The concentration of the lithium salt is preferably 0.8 to 1.8 mol per 1 L of the solvent.
[0038] <Example> The present disclosure will be further described below with reference to examples, but the present disclosure is not limited to these examples.
[0039] <Example 1> [Synthesis of positive electrode active material] LiMnO2, Li2MnO3, LiNiO2, SrO, CaO, and Y2O3 were mixed to a stoichiometric ratio of 3:4:3:0.04:0.04:0.02, and the mixture was placed in a 45cc zirconia pot containing zirconia balls with a diameter of 5 mm. The mixture was placed in a planetary ball mill (FRITSCH, product name "PLP-7") and ground and mixed for 12 hours at a revolution speed of 600 rpm. The mixture was placed in a firing furnace and fired in air at 900°C for 1 hour to obtain a positive electrode active material.
[0040] The composition of the obtained positive electrode active material was analyzed using an inductively coupled plasma (ICP) emission spectrometer (manufactured by Thermo Fisher Scientific, product name "iCAP6300"), and the results showed that Li 1.17 Mn 0.58 Ni 0.25 Sr 0.01 Ca 0.01 Y 0.01 O 2.035 It was.
[0041] [Preparation of positive electrode] The positive electrode active material, acetylene black, and polyvinylidene fluoride (PVdF) were mixed in a mass ratio of 92:5:3, and N-methyl-2-pyrrolidone (NMP) was used as a dispersion medium to prepare a positive electrode composite slurry. Next, this positive electrode composite slurry was applied to the surface of a positive electrode core made of aluminum foil, and the coating was dried and compressed, and then cut into a predetermined electrode size to produce a positive electrode in which a positive electrode composite layer was formed on the positive electrode core.
[0042] [Preparation of non-aqueous electrolyte] A non-aqueous electrolyte solution was prepared by dissolving LiPF6 at a concentration of 1 mol / L in a mixed solvent in which fluoroethylene carbonate (FEC) and methyl 3,3,3-trifluoropropionate (FMP) were mixed in a mass ratio of 1:3.
[0043] [Preparation of test cell] An electrode assembly was prepared by attaching lead wires to the positive electrode and the Li metal counter electrode, and arranging the positive electrode and the counter electrode facing each other via a polyolefin separator. The electrode assembly and the nonaqueous electrolyte were enclosed in an exterior body made of an aluminum laminate film to prepare a test cell.
[0044] <Example 2> A positive electrode active material was synthesized in the same manner as in Example 1, except that LiMnO2, Li2MnO3, LiNiO2, SrO, CaO, and SnO were mixed in a stoichiometric ratio of 3:4:3:0.04:0.04:0.04. The composition of the obtained positive electrode active material was analyzed, and the results showed that Li 1.17 Mn 0.58 Ni 0.25 Sr 0.01 Ca 0.01 Sn 0.01 O 2.03 Moreover, a test cell was produced in the same manner as in Example 1 using the positive electrode active material.
[0045] <Example 3> A positive electrode active material was synthesized in the same manner as in Example 1, except that LiMnO2, Li2MnO3, LiNiO2, SrO, CaO, Y2O3, and SnO were mixed in a stoichiometric ratio of 3:4:3:0.03:0.03:0.015:0.03. Analysis of the composition of the obtained positive electrode active material revealed that Li 1.17 Mn 0.58 Ni 0.25 Sr 0.0075 Ca 0.0075 Y 0.0075 Sn 0.0075 O 2.03375 Moreover, a test cell was produced in the same manner as in Example 1 using the positive electrode active material.
[0046] <Example 4> A positive electrode active material was synthesized in the same manner as in Example 1, except that LiMnO2, Li2MnO3, LiNiO2, SrO, CaO, Y2O3, and ZnO were mixed in a stoichiometric ratio of 3:4:3:0.03:0.03:0.015:0.03. Analysis of the composition of the obtained positive electrode active material revealed that Li 1.17 Mn 0.58 Ni 0.25 Sr 0.0075 Ca 0.0075 Y 0.0075 Zinc 0.0075 O 2.03375 Moreover, a test cell was produced in the same manner as in Example 1 using the positive electrode active material.
[0047] <Example 5> A positive electrode active material was synthesized in the same manner as in Example 1, except that LiMnO2, Li2MnO3, LiNiO2, SrO, CaO, and Y2O3 were mixed in a stoichiometric ratio of 3:4:3:0.02:0.02:0.01. Analysis of the composition of the obtained positive electrode active material revealed that Li 1.17 Mn 0.58 Ni 0.25 Sr 0.005 Ca 0.005 Y 0.005 O 2.0175 Moreover, a test cell was produced in the same manner as in Example 1 using the positive electrode active material.
[0048] <Example 6> A positive electrode active material was synthesized in the same manner as in Example 1, except that LiMnO2, Li2MnO3, LiNiO2, SrO, and CaO were mixed in a stoichiometric ratio of 3:4:3:0.04:0.04. Analysis of the composition of the obtained positive electrode active material revealed that Li 1.17 Mn 0.58 Ni 0.25 Sr 0.01 Ca 0.01 O 2.02 Moreover, a test cell was produced in the same manner as in Example 1 using the positive electrode active material.
[0049] <Example 7> A positive electrode active material was synthesized in the same manner as in Example 1, except that LiMnO2, Li2MnO3, LiNiO2, SrO, CaO, and SnO were mixed in a stoichiometric ratio of 3:4:3:0.02:0.02:0.02. The composition of the obtained positive electrode active material was analyzed, and the results showed that Li 1.17 Mn 0.58 Ni 0.25 Sr 0.005 Ca 0.005 Sn 0.005 O 2.015 Moreover, a test cell was produced in the same manner as in Example 1 using the positive electrode active material.
[0050] <Example 8> A positive electrode active material was synthesized in the same manner as in Example 1, except that LiMnO2, Li2MnO3, LiNiO2, SrO, and CaO were mixed in a stoichiometric ratio of 3:4:3:0.04:0.08. Analysis of the composition of the obtained positive electrode active material revealed that Li 1.17 Mn 0.58 Ni 0.25 Sr 0.01 Ca 0.02 O 2.03 Moreover, a test cell was produced in the same manner as in Example 1 using the positive electrode active material.
[0051] <Example 9> A positive electrode active material was synthesized in the same manner as in Example 1, except that LiMnO2, Li2MnO3, LiNiO2, CaO, and SnO were mixed in a stoichiometric ratio of 3:4:3:0.04:0.08. Analysis of the composition of the obtained positive electrode active material revealed that Li 1.17 Mn 0.58 Ni 0.25 Ca 0.01 Sn 0.02 O 2.03 Moreover, a test cell was produced in the same manner as in Example 1 using the positive electrode active material.
[0052] <Example 10> A positive electrode active material was synthesized in the same manner as in Example 1, except that LiF, LiMnO2, Li2MnO3, LiNiO2, SrO, CaO, and SnO were mixed in a stoichiometric ratio of 0.18:1:1:1:0.036:0.036:0.036. Analysis of the composition of the obtained positive electrode active material revealed that Li 1.17 Mn 0.58 Ni 0.25 Sr 0.01 Ca 0.01 Sn 0.01 O 2.025 F 0.005 Moreover, a test cell was produced in the same manner as in Example 1 using the positive electrode active material.
[0053] <Comparative Example> A positive electrode active material was synthesized in the same manner as in Example 1, except that LiMnO2, Li2MnO3, and LiNiO2 were mixed in a stoichiometric ratio of 3:4:3. 1.17 Mn 0.58 Ni 0.25 The positive electrode active material was used to prepare a test cell in the same manner as in Example 1.
[0054] [Evaluation of initial voltage and voltage retention rate during charge / discharge cycles] The test cells of the examples and comparative examples were charged to 4.7 V at a constant current of 0.2 C in a temperature environment of 25° C., and then discharged to 2.5 V at a constant current of 0.5 C. From the discharge curve at this time, the initial voltage was calculated by the following formula.
[0055] Initial voltage = (discharge energy, which is the sum of the electrical quantities at each voltage) / (discharge capacity at 2.5V) As above, the battery was charged to 4.7 V at a constant current of 0.2 C and then discharged to 2.5 V for 50 cycles. From the discharge curve at the 50th cycle, the battery voltage at the 50th cycle was calculated using the above formula, and the voltage retention rate was calculated using the following formula.
[0056] Voltage retention rate = (battery voltage at 50th cycle) / (initial voltage) The results of the initial voltage and voltage retention rate of the test cells of the examples and comparative examples are summarized in Table 2. The elements contained in Me and their molar fractions are also shown in Table 2. Note that a higher value of the voltage retention rate indicates that the decrease in the battery voltage due to the charge / discharge cycles is more suppressed.
[0057] [Table 2]
[0058] The test cells of Examples 1 to 10 had a higher voltage retention ratio while maintaining the same initial voltage compared to the test cells of the Comparative Examples not containing Me. The initial voltages of Examples 1 to 3 were also higher than those of the Comparative Examples. [Explanation of symbols]
[0059] 10 Secondary battery 11 Positive electrode 12 Negative electrode 13 Separator 14 Electrode body 15 Exterior body 16 Sealing body 17,18 Insulating plate 19 Positive lead 20 Negative lead 21 Grooved part 22 Filters 23 Lower valve body 24 Insulating materials 25 Upper valve 26 Cap 26a opening 27 Gasket
Claims
1. A positive electrode active material for a non-aqueous electrolyte secondary battery, comprising a lithium transition metal composite compound, The lithium transition metal complex compound is a Li-excess system and has the general formula Li x Mn y Ni z Me α O a F b (wherein 1≦x≦1.2, 0.4≦y≦0.8, 0≦z≦0.4, x+y+z=2, 0<α≦0.05, 1.8≦a≦2, 1.8≦a+b≦2.2, and Me represents at least two or more elements selected from metal elements excluding Li, Mn, and Ni), The positive electrode active material for a non-aqueous electrolyte secondary battery, wherein Me is an element having an ionic radius of 0.6 Å or more.
2. 2. The positive electrode active material for a nonaqueous electrolyte secondary battery according to claim 1, wherein Me contains at least one element selected from the group consisting of K, Sr, Ba, Bi, Ca, La, Pr, Y, Dy, Sn, and Zn.
3. 2. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein Me contains at least one element selected from the group consisting of Sr, Ca, Y, and Sn.
4. 2. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the Me consists essentially of at least three elements selected from the group consisting of Sr, Ca, Y, and Sn.
5. 2. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the Me contains at least an alkaline earth metal element.
6. 6. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the α satisfies 0.01≦α≦0.
03.
7. 7. A non-aqueous electrolyte secondary battery comprising a positive electrode containing the positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, a negative electrode, and a non-aqueous electrolyte.
Citation Information
Patent Citations
Manufacture of CMOS type semiconductor device
JP1988042161A
Positive electrode active material for lithium secondary battery and its manufacturing method, and lithium secondary battery using it
JP2002008660A
Positive electrode active material and non-aqueous electrolyte secondary battery containing the same
JP2004087487A
Positive active material, its manufacturing method, and battery
JP2006351487A
High-voltage thin-layer cathode material for lithium rechargeable batteries and its preparation
JP2007516583A